(untitled) (Journal of Engineering, 2002)
This paper describes a stego system in which a gray scale image is embedded in another one.Wavelet transform of both the cover image and the embedded image is used to sort their subbands energies to guarantee that the embedded image will be inserted in the low frequency components of the cover image with little perceptual distortion. Embedding by this way increases the robustness of the system but affects the syster 1 imperceptibility, so a variable scaling factor (a) is used to attenuate the components of the embedded image before adding them to those of the cover image. It is found that the stego image with peak signal-to-noise ratio (PSNR) of about 30 dB has goo 1 imperceptibility.The attacker is proposed to be active, so compression is applied to the stego image. According to this, the scaling factor must be increased to compromise between the quality of the stego and the reconstructed images. This increment reduces the imperceptibility of the stego image and here the trade off between the imperceptibility and the robustness occurs.The attack is proposed to be stego known, so that to increase the security of the system, a stego key is generated from the embedded image itself and is transmitted separately, making the system type secret key steganography.The size of the embedded image obtained in the work is one quarter the size of the cover image that may be considered good comparing with the available systems.